A SOCIOLINGUISTIC ANALYSIS OF EMOTICON USAGE IN JAPANESE BLOGS: VARIATION BY AGE, GENDER, AND TOPIC - Nishimura, Yukiko (AoIR Selected Papers of Internet Research, 2015)
This study explores how Japanese older men and women express themselves in blogging (Curtain 2004), when aging population (65 years and up) is sharply on the rise. The internet proliferation among senior users is also rapidly increasing. In this demographic trend, though younger people’s online activities have heavily been studied, how senior users engage in online activities needs research (Smith 2014) both in the US and Japan. This study specifically examines understudied senior users’ linguistic behavior online from a sociolinguistic perspective (Coupland 2004). This paper is comprised of two parts. Part I makes a quantitative discussion on differences in linguistic and discourse specific features of emoticons between older and younger users for both genders, with respect to their diary-type blogs on everyday topics. Part II makes a qualitative analysis on blogs that discusses a specific topic, moral harassment, and examines how blogging on this particular topic differs from blogging on everyday topics, the latter of which comes from a subset used for the quantitative analyses. The study finds emoticon as the most salient feature that distinguishes younger and older men’s and women’s blogging, and blog topics as a determining factor on emoticon uses.